2019
DOI: 10.3389/fphar.2019.01420
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of Serine Proteases to Reduce Cardiac Inflammation and Fibrosis in Atrial Fibrillation

Abstract: Systemic inflammation correlates with an increased risk of atrial fibrillation (AF) and thrombogenesis. Systemic inflammation alters vessel permeability, allowing inflammatory and immune cell migration toward target organs, including the heart. Among inflammatory cells infiltrating the atria, macrophages and mast cell have recently attracted the interest of basic researchers due to the pathogenic mechanisms triggered by their activation. This chemotactic invasion is likely implicated in shortand long-term chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 183 publications
(224 reference statements)
0
12
0
Order By: Relevance
“…Taking into account its hepatoprotective effect, ferulic acid has been shown to decrease the elevated serum levels of the liver marker enzymes, AST and ALT, in rats subjected to ethanol-induced hepatotoxicity [3]. Additionally, azetidin-2-ones have shown good inhibitory activity on human chymase-a chymotrypsin-like serine protease which is thought to play an important role in chronic inflammation [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account its hepatoprotective effect, ferulic acid has been shown to decrease the elevated serum levels of the liver marker enzymes, AST and ALT, in rats subjected to ethanol-induced hepatotoxicity [3]. Additionally, azetidin-2-ones have shown good inhibitory activity on human chymase-a chymotrypsin-like serine protease which is thought to play an important role in chronic inflammation [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cytokines, chemokines, and CAMs, inflammatory mediators also include enzymes, which play a crucial role in tissue remodeling and inflammatory response. Activated leukocytes and mast cells express a variety of proteolytic enzymes, particularly serine proteases that ultimately modulate an inflammatory response [ 167 ].…”
Section: Cross-talk Between Nrf2 and Inflammationmentioning
confidence: 99%
“…Important etiologies of AF include surgical procedures [ 1 ], hyperthyroidism [ 2 ], myocardial infarction [ 3 ], and cardiomyopathies [ 4 ]. Although the potential pathophysiologic mechanisms of AF remain controversial, there has been increasing evidence that inflammation is involved in the pathogenesis of AF [ 5 7 ]. Laboratory tests showed that inflammatory biomarkers (high-sensitivity C-reactive protein) increased in patients with AF [ 8 ] and anti-inflammatory medications may reduce the morbidity of AF [ 9 ].…”
Section: Introductionmentioning
confidence: 99%